THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION: A CASE STUDY OF THE PERFORMANCE OF RADIO REPUBLIK INDONESIA (RRI) IN CIREBON - Adelia, Adelia; Selviana, Selviana; Rahmawati, Fitri; Romdony, Jefry (Ridwan Institute, 2024)
The purpose of this study is to investigate the effect of the service quality of Radio Republik Indonesia (RRI) in Cirebon on the level of customer satisfaction. The study was conducted through an observational interview. The interviews were conducted to get first-hand views and experiences from RRI customers regarding the quality of service they received and their satisfaction level. It was found that aspects such as broadcast program quality, sound quality, staff friendliness, and ease of access to information were the main factors that contributed to customer satisfaction, which shows that the high quality of services provided by the radio station will increase customers' satisfaction. This study can be used as a theoretical foundation for further research in this area and a reference for other broadcasting organizations interested in improving their customer experience. It can also enrich the literature on service quality management and customer satisfaction in the media and communication sectors.